Recent advances in transition metal-catalysed hydroacylation of alkenes and alkynes. Issue 5 (17th February 2016) - Ghosh, Avipsa; Johnson, Kirsten F.; Vickerman, Kevin L.; Walker, James A.; Stanley, Levi M.
Abstract : This highlight presents advances in transition metal-catalysed alkene and alkyne hydroacylation over the past three years. Abstract : This highlight discusses developments in transition metal-catalysed alkene and alkyne hydroacylation reactions over the past three years. The discussion summarizes the development of new catalyst systems for alkene and alkyne hydroacylation and applications to the synthesis of important ketone building blocks. The highlight captures transition metal-catalysed alkene and alkyne hydroacylation at a time of impressive growth when cobalt, nickel, ruthenium, and iridium catalysts are emerging as complements or replacements for traditional rhodium catalysts.